Trade, Violence and Diplomacy on the Coast of Ikorodu: The Resistance of Balogun Mabadeje Jaiyesimi - Adebowale Adeyemi-Suenu (Yoruba Studies Review)
From the 1850s, British influence in Lagos and coastal Nigeria expanded, leading to the annexation of Lagos in December 1861 and the establishment of Lagos Colony in 1862. This period also witnessed the British quest for the control of coastal and inland trade routes. Ikorodu’s location north of Lagos and on the lagoon, and its control of trade from the coast to Sagamu, the main city of Remo, involved the town in larger struggles between the Ijebu kingdom and the Egba settlers at Abeokuta, and in the expansionist plans for Lagos under Governor Henry Stanhope Freeman (1862–4) and his successor, Captain John Hawley Glover (1864–6).